Position sensitivity in 3"×3" Spectroscopic LaBr3:Ce Crystals. (May 2015) - Blasi, N; Giaz, A; Boiano, C; Brambilla, S; Camera, F; Million, B; Riboldi, S
Abstract: The position sensitivity of a thick, cylindrical and continuous 3" × 3" (7.62 cm × 7.62 cm) LaBr3 :Ce crystal with diffusive surfaces was investigated. Nuclear physics basic research uses thick LaBr3 :Ce crystals (> 3cm) to measure medium or high energy gamma rays (0.5 MeV < Eγ < 20 MeV). In the first measurement the PMT photocathode entrance window was covered by black absorber except for a small window 1 cm × 1cm wide. A complete scan of the detector over a 0.5 cm step grid was performed. The data show that even in a 3" thick LaBr3 :Ce crystal with diffusive surfaces the position of the full energy peak centroid depends on the source position. The position of the full energy peak centroids are sufficient to identify the collimated gamma source position. The crystal was then coupled to four Position Sensitive Photomultipliers (PSPMT). We acquired the signals from the 256 segments of the four PSPMTs grouping them into 16 elements. An event by event analysis shows a positon resolution of the order of 2 cm.